URDU-ORIENTALISTS AND BATTLES OF PROPHET MUHAMMADﷺ - Dr. Arshad Munir; Abdul Hameed Arain; Dr. Kareem Dad (دی اسکالر)
With the down of Quresh of Makkah and other non-believers stood against Islam and started propagations against Prophet Muhammad (peace be upon him). In the result of propagation Non-believers attacked on Muslims and Prophet himself also.To save Muslims and Islam from their propagation Prophet fought wars against them in self-defence. During life span of Prophet (peace be upon him) 86 deputations were sent, these are called ‘sirya سِریہ’ and in which expeditions Prophet himself took part these are called ‘Ghazwat غزوات’, total ghazwat are 28. Westerns still are propagating that Islam spread with these wars. Prophet (peace be upon him) attacked non-Muslims and compelled them to accept Islam, this is the only cause of spreading of Islam. There is nothing in bottom of this propagation. If we consider the history and autobiography of Prophet Muhammad (peace be upon him) and review this propagation critically. We find that these wars were fought only in self-defense, to protect innocent and poor people and keep peace in the territory.